Effect of rootstock on yield, grape composition and wine sensory attributes of Shiraz grown in a moderately saline environment. (12th September 2019) - Walker, R.R.; Blackmore, D.H.; Clingeleffer, P.R.; Holt, H.; Pearson, W.; Francis, I.L.
Abstract: Background and Aims: The study compared the viticultural performance and wine sensory attributes of Shiraz grafted on eight rootstocks with a range in vine vigour and grown under drip‐irrigation with moderately saline water. Methods and Results: The rootstocks were 140 Ruggeri, 1103 Paulsen, 110 Richter, Ramsey, 101‐14, M5489, M5512 and M6262. Ramsey and 140 Ruggeri had the highest leaf area index and M6262 the lowest. Ramsey had highest yield, followed by 140 Ruggeri > M5489 = 110 Richter > M5512 > 1103 Paulsen = 101‐14 > M6262. Rootstock M6262 had highest wine chloride concentration of 482 and 384 mg/L in 2012 and 2013, respectively, but salty taste and a thickness mouthfeel (viscosity) were significant only in 2012. Wines from the other seven rootstocks had a chloride and sodium concentration under 175 and 40 mg/L, respectively. Colour density was highest in wine from 101‐14 in 2012 and from 101‐14, 1103 Paulsen and M5489 in 2013. A salt tolerance index (STI) for the eight rootstocks was calculated based on yield, leaf area index, grape juice chloride and sodium concentration and wine colour density. Conclusions: Rootstock M6262 had lowest STI in both years. M5489 had highest STI in 2013 followed by 110 Richter = M5512 = 101‐14 = 140 Ruggeri. The recognition threshold for salty taste may lie between a chloride concentration in wine of between 384 and 482 mg/L. Significance of the Study: The STI, based on five wine grape performance parameters, provides a promising measure of rootstock salt tolerance compared with the traditional parameters of yield and/or capacity for salt exclusion.